Modal transformation applied to double three-phase transmission lines - Prado, A. J.; Kurokawa, S.; Pissolato, J.; Bovolato, F.; Tavares, MCD; Portela, C. M. (IEEE, 2004)
Double three-phase transmission lines are analyzed in this paper using a modal transformation model. The main attribute of this model is the use of a single real transformation matrix based on line geometrical characteristics and the Clarke matrix. Because of this, for any line point, the electrical values can be accessed for phase domain or mode domain using the considered transformation matrix and without convolution methods. For non-transposed symmetrical lines the errors between the model results and the exact modes are insignificant values. The eigenvector and eigenvalue analyses for transposed lines search the similarities among the three analyzed transposition types and the possible simplifications for a non-transposed case.
Keywords: Clarke matrix; eigenvector; eigenvalue; frequency; mode domain; transformation matrix; transmission lines